Vocabulary Instruction for Students with Learning Disabilities: A Review of the Research - Bryant, Diane Pedrotty; Goodwin, Marilyn; Bryant, Brian R.; Higgins, Kellie (Learning disability quarterly, 2003)
This article reviews research on vocabulary interventions involving students with learning disabilities. The purpose of the review was to summarize the findings of vocabulary intervention research and to present implications for vocabulary instruction. The studies were analyzed based on the following intervention research variables: word selection procedure, materials, instructional design and procedures, duration of the intervention, mastery criterion, measures of vocabulary learning (word knowledge level and reading comprehension), maintenance, and generalization (reading comprehension). Based on the selection criteria, six articles spanning the period from 1978 to the present were identified. Vocabulary interventions were categorized into four areas, computer-assisted instruction (CAI), fluency-building vocabulary practice activities, mnemonic strategy instruction, and concept enhancement instruction. Overall, positive results were found for the interventions on measures of immediate recall, maintenance, and generalization.